Simtom Depresi dan Diabetes Mellitus: sebuah Comorbidity - Jenita DT Donsu (Faculty of Psychology Universitas Gadjah Mada, 2012)
Each individual has a great hope to enjoy good health throughout his life, but it is notuncommon anxiety and stress become a part of life that is often continuous, thus causingdepression. Depression is a mental disorder that affects most people, and can attack all levels ofsociety of all ages, gender, social status, or economic status. Depression is closely related to chronicdiseases including diabetes mellitus. Critical review of theories and models is the first step toprepare supporting theories to a study. Theories that have been collected are: stress, anxiety, andself-esteem. Based on these theories are found a variety of approaches such as: (1) a cognitivebehavioral approach to overcoming depression, (2) cognitive approach to recognize the variousfaults, in order to evaluate and reduce the emotional disturbance associated with depressivesymptoms; (3) approach the theoretical model to recognize, understand, and treating depression indiabetes mellitus.